STUDI EKSPERIMEN PENGARUH WAKTU PENUANGAN ADUKAN BETON READYMIX KE DALAM FORMWORK TERHADAP MUTU BETON NORMAL - Putra, Hardiyanto Eka; Sardjana, Dharma; Samsurizal, Eddy (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2017)
In the manufacture of the test object, the method used is the method of SNI 2002. The cement used is a cement PPC. The test object is made cylindrical with Ã† 15 cm, and 30 cm high of 7 pieces, and a cube of 15 cm x 15 cm x 15 cm as many as 120 pieces. There are eight variations of concrete sample that is normal with old concrete pouring slurry into formwork for 0 minutes, 30 minutes, 60 minutes, 90 minutes, 120 minutes, 150 minutes, 180 minutes and 210 minutes. Testing / testing specimen include compressive strength test, test setting time, test temperature and shrinkage and elastic modulus test. From the research the compressive strength characteristics of normal concrete with a foundry 0 minutes, 30 minutes, 60 minutes, 90 minutes, 120 minutes, 150 minutes, 180 minutes, 210 minutes, respectively produce compressive strength of concrete characteristics average (28 days) 319, 51 kg / cm2, 326.30 kg / cm2, 320.26 kg / cm2, 324.04 kg / cm2, 320.26 kg / cm2, 312.71 kg / cm2, 318 kg / cm2, and 259.83 kg / cm2. Modulus of Elasticity average normal concrete with casting time of 0 minutes, 30 minutes, 60 minutes, 90 minutes, 120 minutes, 150 minutes, 180 minutes, respectively produce Mpa 21614.38, 15691.11 MPa, 20527.44 MPa, 25 097 , 62 Mpa, 26718.54 MPa, MPa 23446.83, 23446.83 MPa. It can be concluded that the longer the time of stirring and pouring concrete into formwork, the compressive strength value produced will decrease. Keyword: pouring slurry, compressive strength, pull out, modulus of elasticity.